Integrative Network Pharmacology Unveils Limonia acidissima as a Potential Natural Product for Targeting Cancer - Wahyuni, Reni Sri; Muchlisin, M. Artabah; Jamil, Ahmad Shobrun; Astuti, Engrid Juni; Rafikayanti, Agustin (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
Cancer remains a formidable health challenge worldwide, with complex molecular mechanisms driving its initiation, progression, and therapeutic resistance. In this study, we employed bioinformatics analyses to elucidate the molecular underpinnings of cancer biology, focusing on Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analysis. Our GO analysis revealed the enrichment of key biological processes such as protein phosphorylation, regulation of programmed cell death, and transmembrane receptor signaling pathways, underscoring the critical roles of signaling cascades and regulatory mechanisms in tumorigenesis. Similarly, molecular functions such as protein kinase activity and ATP binding were identified as significantly enriched, highlighting the importance of protein kinases and molecular interactions in cancer development and progression. The KEGG pathway analysis further delineated dysregulated signaling pathways associated with cancer, including the MAPK and PI3K-Akt signaling pathways, implicating these pathways as central regulators of cancer progression. These findings deepen our understanding of cancer biology and offer potential targets for therapeutic intervention. Integrating multi-omics data and systems biology approaches may provide deeper insights into the intricate networks underlying cancer pathogenesis, paving the way for developing more effective treatments for cancer patients.